Screened out - Baudrillard, Jean (Verso, 2002)
In this collection of journalistic essays the philosopher Jean Baudrillard turns his hand to topical political debates and issues, Jean Baudrillard addresses subjects ranging from those he has already established as his trademark (virtual reality, Disneyworld, television) to more unusual topics such as the Western intervention in Bosnia, Holocaust revisionism, AIDS and genetic cloning. These articles are corruscating and intriguing, not least because they show that Baudrillard is still susceptible and alert to influences from social movements and the world beyond the hyper-real.